A nervous night - Manushkin, Fran.; Lyon, Tammie (Minneapolis, MN : Picture Window Books, 2010)
Katie is nervous about a sleepover at her grandparents' house.
2.3
K-3
K-3
510L
Keywords: Sleepovers -- Juvenile fiction; Grandparents -- Juvenile fiction; Chinese Americans -- Juvenile fiction; Sleepovers -- Fiction; Grandparents -- Fiction; Chinese Americans -- Fiction; Sleepovers -- Fiction; Grandparents -- Fiction; Chinese Americans -- Fiction; Readers (Elementary)